International Food Policy Research Institute (IFPRI) Datasets Terms of Use Statement - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
The International Food Policy Research Institute (IFPRI) views the products of its research including research dataset(s) as global public goods and is committed to enabling their widespread distribution and use by providing unrestricted public access. This is in keeping with the IFPRI Research Data Management and Open Access (RDMOA) Policy and the CGIAR Open Access and Data Management Policy (each, a “Policy” and together, the “Policies”). IFPRI makes all its research data publicly available through the “IFPRI Dataverse.” The IFPRI Dataverse houses and is comprised of datasets collected during the course of IFPRI research, including data tables in various standard formats, survey instruments, codebooks, metadata, and other associated documentation. IFPRI Dataverse is a network member of Harvard Dataverse, which is a repository for research data hosted at Institute for Quantitative Social Science (IQSS)1, Harvard University. IFPRI is the owner of the “IFPRI Dataverse” (sometimes referred to in these Terms of Use as the “Site”). The Communications and Public Affairs (CPA) division of IFPRI operates this Site on behalf of IFPRI. For questions pertaining to these terms of use, licenses, or concerns, please contact IFPRI-Data@cgiar.org. In the event of any conflict between these Terms of Use and either of the Policies, the terms of the applicable Policy shall control with respect to, and to the extent of, any such conflicting terms.